Comparing Instructional Approaches in Caregiver-Implemented Intervention: An Interdisciplinary Systematic Review and Meta-Analysis. (December 2021) - Sone, Bailey J.; Lee, Jordan; Roberts, Megan Y.
Family involvement is a cornerstone of early intervention (EI). Therefore, positive caregiver outcomes are vital, particularly in caregiver-implemented interventions. As such, caregiver instructional approaches should optimize adult learning. This study investigated the comparative efficacy of coaching and traditional caregiver instruction on caregiver outcomes across EI disciplines. A systematic search for articles was conducted using PRISMA guidelines. Meta-analysis methodology was used to analyze caregiver outcomes, and a robust variance estimate model was used to control for within-study effect size correlations. Seven relevant studies were ultimately included in the analysis. A significant, large effect of coaching on caregiver outcomes was observed compared to other models of instruction ( g = 0.745, SE = 0.125, p = .0013). These results support the adoption of a coaching framework to optimize caregiver outcomes in EI. Future research should examine how coaching and traditional instruction can be used in tiered intervention models with a variety of populations.